2000
DOI: 10.1159/000023505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Growth Hormone and Oxandrolone Treatment on Glucose Metabolism in Turner Syndrome

Abstract: In 18 girls with Turner syndrome, glucose tolerance was studied before treatment and after 6 and 24 months of growth-promoting treatment with recombinant human growth hormone (24 IU/m2/week; 8 mg/m2/week) and oxandrolone (0.06 mg/kg/day), as well as after termination of the treatment. One girl developed an overt non-ketotic diabetes mellitus 50 months after termination of treatment. The results of the remaining 17 girls in whom the effect of treatment on glucose metabolism was reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Furthermore, after ending GH treatment, insulin levels and the indices for relative insulin resistance (30Ј and 120Ј ratios for insulin/glucose) fell but only to a point above pretreatment levels. Similar results have been found previously in children with idiopathic short stature and in girls with TS after discontinuation of GH treatment (18,19). Moreover, we show that stimulated insulin levels after discontinuation were comparable with normal postpubertal girls.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, after ending GH treatment, insulin levels and the indices for relative insulin resistance (30Ј and 120Ј ratios for insulin/glucose) fell but only to a point above pretreatment levels. Similar results have been found previously in children with idiopathic short stature and in girls with TS after discontinuation of GH treatment (18,19). Moreover, we show that stimulated insulin levels after discontinuation were comparable with normal postpubertal girls.…”
Section: Discussionsupporting
confidence: 91%
“…Fasting glucose levels have been found unchanged during GH treatment in most studies [21][22][23][24][25][26], but increased in others [27], while a dose response study only found increased fasting glucose in the group that received the highest GH doses [25]. The values returned to baseline values after termination of GH [25].…”
Section: Glucose Metabolism During Gh Treatmentmentioning
confidence: 96%
“…One explanation could be reduced insulin sensitivity. The insulin levels decrease after termination of GH, but do not return to levels as low as before treatment [21,25,28]. This could be an irreversible effect of GH, but could also be due to the fact that both fasting insulin and area under the curve for insulin (AUC I ) increases with age, particularly during adolescence [31].…”
Section: Glucose Metabolism During Gh Treatmentmentioning
confidence: 99%
See 2 more Smart Citations